Clinical-epidemilogical characterization of patients with leptopirosis in the Cumanayagua Municipality. Cienfuegos Province. 2007-2017 - Narciso Águila Rodríguez; Hilda María Delgado Acosta; Tamara Montenegro Calderón; Delfín Rodríguez Buergo; Lizette Rodríguez Fernández; Rosario Rodríguez Castro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: leptospirosis still is the most prequent zoonosis worldwide. Objective: to characterize clinically and epidemiologically patients with leptospirosis. Methods: Observational descriptive method which included 38 cases diagnosed leptospirosis in the Cumanayagua Municipality, Cienfuegos Province in the period 2207- 2017. The variables used were year and month of the diagnosis, age sex, precedence, vaccination antecedents, possible source of infection, signs, symptoms and complications. Data was collected from chronological series and epidemiological histories at the Municipal Center of Hygiene and Epidemiology. Data processing was done with Excel and percentages and incidence rates were used. Results: during the period 2072 patients were reported as suspected to have the disease and only 38 were confirmed. The highest rate was in 2013 with 42.1%. Only 15% had antecedents of being vaccinated with the anti- leptospirosis vaccine. The infection source of higher incidence was to be an agricultural worker with 47.4%, followed by contact with animals 28.9%. Among the most frequent symptoms were fever, chephalalgias, myalgias and arthralgias. Conclusion: a sub-registration in the serological diagnosis of the cases., occupational risks with contact to agricultural activities and predominance of clinical anicteric form.